2000
DOI: 10.1002/(sici)1098-2264(200006)28:2<138::aid-gcc2>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

MOZ is fused top300 in an acute monocytic leukemia with t(8;22)

Abstract: We report on the fusion of the monocytic leukemia zinc finger protein (MOZ) gene to the adenoviral E1A‐associated protein p300 (p300) gene in acute monocytic leukemia M5 associated with a t(8;22)(p11;q13) translocation. We studied two patients with double‐color fluorescence in situ hybridization (FISH) using the yeast artificial chromosome 176C9 and the bacterial artificial chromosome clone H59D10 specific to the MOZ and p300 genes, respectively. Both probes were split in the patients' chromosome metaphase cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(104 citation statements)
references
References 36 publications
2
101
0
1
Order By: Relevance
“…MOZ-CBP lacks the SM domain of MOZ, but gains almost all of CBP (Figure 3a). Mirroring the homology between p300 and CBP, the MOZ gene is fused to that of p300 in translocation t(8;22)(p11;q13) (Chaffanet et al, 2000;Kitabayashi et al, 2001b). Moreover, in t(10;16)(q22;p13) associated with childhood AML or therapeutic myelodysplastic syndromes, the MORF gene on 10q22 (Champagne et al, 1999) is fused to that of CBP (Panagopoulos et al, 2001;Kojima et al, 2003).…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 99%
“…MOZ-CBP lacks the SM domain of MOZ, but gains almost all of CBP (Figure 3a). Mirroring the homology between p300 and CBP, the MOZ gene is fused to that of p300 in translocation t(8;22)(p11;q13) (Chaffanet et al, 2000;Kitabayashi et al, 2001b). Moreover, in t(10;16)(q22;p13) associated with childhood AML or therapeutic myelodysplastic syndromes, the MORF gene on 10q22 (Champagne et al, 1999) is fused to that of CBP (Panagopoulos et al, 2001;Kojima et al, 2003).…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 99%
“…Recent biochemical purifications revealed that both the Drosophila and mammalian MOF proteins reside in multi-protein complexes and that most of these interacting proteins are conserved between Drosophila and mammals (Table 2; Dou et al, 2005;Smith et al, 2005;Mendjan et al, 2006). Co-purification of four human MSL proteins (hMSL1, hMSL2, hMSL3 and hMOF) showed that the MSL (Borrow et al, 1996;Carapeti et al, 1998;Champagne et al, 1999Champagne et al, , 2001Chaffanet et al, 2000;Kitabayashi et al, 2001;Pelletier et al, 2002;Bristow and Shore, 2003;Deguchi et al, 2003;Kindle et al, 2005;Katsumoto et al, 2006;Thomas et al, 2006;Ohta et al, 2007 Abbreviation: HAT, histone acetyltransferases.…”
Section: The Histone Acetyltransferase Mofmentioning
confidence: 99%
“…Some cases have been previously reported in detail, namely M45-1, M45-3, M45-4, M45-5, M45-7, M45-11, M45-13, M45-16, M45-19, M45-20, M45-21, M45-23, M45-26, 7 M45-052, 13 M45-031, 14 M45-032 6 M45-062 and M45-063. 4 Three BM samples were used as normal controls (normal bone marrow (NBM)). They were collected from breast cancer patients without micrometastases.…”
Section: Patientsmentioning
confidence: 99%
“…It fuses two genes encoding histone acetyltransferases (HAT), MYST3 (also called MOZ) located at 8p11 to CREBBP (also called CBP) located at 16p13. [1][2][3] Variant translocations involve other HAT-encoding genes, such as EP300 at 22q13, 4 MYST4 at 10q22, NCOA2 at 8q13 5 or NCOA3 at 20q12. 6 MYST3-linked acute myeloid leukemias (AMLs) share specific features, such as frequent extramedullary involvement, disseminated intravascular coagulation, erythrophagocytosis and a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%